2015
DOI: 10.1007/s11920-015-0618-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Depression: Does Inflammation Play a Role?

Abstract: Women become depressed more frequently than men, a consistent pattern across cultures. Inflammation plays a key role in initiating depression among a subset of individuals, and depression also has inflammatory consequences. Notably, women experience higher levels of inflammation and greater autoimmune disease risk compared to men. In the current review, we explore the bidirectional relationship between inflammation and depression and describe how this link may be particularly relevant for women. Compared to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 105 publications
8
87
1
5
Order By: Relevance
“…Many factors that are common in the lives of women with physical disabilities, including socioeconomic disadvantage, functional limitations, pain and other chronic health conditions, poor diet, physical inactivity, low self-esteem, and chronic stress, have been linked to higher rates of depression [22]. In addition, women may be more vulnerable to inflammation-induced mood and behavior changes than men [23]. Our results are consistent with the above studies.…”
Section: Discussionsupporting
confidence: 90%
“…Many factors that are common in the lives of women with physical disabilities, including socioeconomic disadvantage, functional limitations, pain and other chronic health conditions, poor diet, physical inactivity, low self-esteem, and chronic stress, have been linked to higher rates of depression [22]. In addition, women may be more vulnerable to inflammation-induced mood and behavior changes than men [23]. Our results are consistent with the above studies.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, that study used a large sample (n = 4585) that was roughly half the size of our study's sample, which may also help to explain why they did not find this effect. The fact that we did not find this relationship in women is surprising given that women are more prone to both psychological distress (Bromet et al, 2011) and inflammation (Yang & Kozloski, 2011), as well as the negative mood and behaviour effects of inflammation (Derry, Padin, Kuo, Hughes, & Kiecolt-Glaser, 2015). However, as previously noted, a number of studies have found that inflammation is more strongly linked to psychological distress in males than in females (Ramsey et al, 2016).…”
Section: Discussionmentioning
confidence: 48%
“…For example, women respond to transient elevations in inflammation with stronger feelings of loneliness and social disconnection than men, a characteristic that likely contributes to the 2:1 ratio of women to men in depressive disorders (Moieni et al, 2015). Additionally, prior depression, somatic symptomatology, interpersonal stressors, childhood adversity, obesity, and physical inactivity are all factors that elevate inflammation, and women have disproportionately higher representation than men in each of these domains (Derry et al, 2015). Relationship-related distress has stronger ties to inflammation among women than men (Derry et al, 2015), and the relationship between depression and marital quality is stronger among women than men (Whisman, 2001).…”
Section: Gender Influencesmentioning
confidence: 99%